أثر التمكين الإداري على الأداء الوظيفي للعاملين: تنمية كفاءات . الموارد البشرية كمتغير وسيط - العويتي Monder Fathi Ahmed; علوي Nahg AbdulMajid; مسعود Khairi Ahmed (مجلة الاصالة, 2025)
The Job Performance Index (KPI) is an indicator that reflects the overall performance of an organization. Therefore, many Libyan companies have adopted management strategies to improve employee performance, including administrative empowerment. This study aims to understand the impact of administrative empowerment on employee performance at the Tripoli Medical Center, as well as the impact of developing human resource competencies as an intervening variable in the relationship between administrative empowerment and job performance. The study used a descriptive quantitative research design. Data were collected using a questionnaire distributed to a simple random sample of 351 employees at the Tripoli Medical Center. The data were analyzed using descriptive statistics using SPSS and structural equation modeling using Amos. The study results showed a statistically significant positive impact of administrative empowerment on job performance. The results also indicated that developing human resource competencies plays a mediating role in strengthening the relationship between administrative empowerment and job performance. The study recommended increasing the efforts of the Tripoli Medical Center management to promote the concept of empowerment by granting employees broader powers, participating in decision-making, and encouraging individual initiative.